Amorphous alloy material, preparation method thereof and magnetic alloy product

By using Fe-based amorphous alloy materials with specific elements proportions and combined with an optimized preparation process, the problems of high cost and time-consuming preparation process of traditional Fe-based amorphous nanocrystalline magnetic core materials are solved, and a low-cost and high-efficiency preparation process is achieved, while maintaining excellent soft magnetic properties.

CN119673605APending Publication Date: 2025-03-21SOUTHERN POWER GRID SENSING TECHNOLOGY (GUANGDONG) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411616665.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the preparation of traditional Fe-based amorphous nanocrystalline magnetic core materials, expensive elements such as cobalt and nickel are required, resulting in high material costs and time-consuming preparation process, reducing production efficiency.

Method used

By using amorphous alloy material with FeaPbBcCdCue (where a, b, c, d, and e represents the atomic percentage of each element, 70≤a≤80, 0≤b≤14, 0≤c≤14, 3≤d≤6, 0

Benefits of technology

It is achieved to maintain the amorphous structure and excellent soft magnetic properties of the Fe-based amorphous nanocrystalline magnetic core material without using cobalt, reduce material costs, simplify the preparation process and improve production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673605A_ABST
    Figure CN119673605A_ABST
Patent Text Reader

Abstract

The invention relates to an amorphous alloy material, a preparation method thereof and a magnetic alloy product. A chemical composition of the amorphous alloy material is FeaPbBcCdCue, a, b, c, d and e represent atomic percentages of elements, 70 < = a < = 80, 0 < = b < = 14, 0 < = c < = 14, 3 < = d < = 6, 0 < e < = 2, and a + b + c + d + e = 100. Elements of the amorphous alloy material comprise specific components with a specific matching relation, and all the components are coordinated and matched through the specific matching relation, so that the amorphous alloy material keeps an amorphous structure and excellent soft magnetic performance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloy material production, and in particular to an amorphous alloy material and a preparation method thereof, and a magnetic alloy product. Background Art

[0002] Fe-based amorphous nanocrystals are a new type of material with unique physical and chemical properties and are widely used in various fields. Fe-based amorphous nanocrystals refer to materials in which amorphous and nanocrystals coexist in iron-based alloys. Compared with traditional crystalline materials, Fe-based amorphous nanocrystals have the following significant characteristics. Fe-based amorphous nanocrystals have excellent mechanical properties. Due to the structural characteristics of amorphous and nanocrystals, Fe-based amorphous nanocrystals have high hardness, high strength and excellent toughness, can maintain structural stability under extreme conditions, and have good magnetic properties. Studies have shown that Fe-based amorphous nanocrystals have the characteristics of high saturation magnetic induction intensity and low magnetic permeability, can show good performance in magnetic fields, and therefore have broad application prospects in the electromagnetic field. Fe-based amorphous nanocrystals also have excellent chemical stability and corrosion resistance. Due to its amorphous and nanocrystal structural characteristics, Fe-based amorphous nanocrystals can resist chemical reactions such as oxidation and corrosion, so they have broad application potential in the chemical industry.

[0003] In the field of research and development of Fe-based amorphous nanocrystalline magnetic core materials, traditional technical means mainly focus on heat treatment near the first crystallization temperature of the alloy material to promote the precipitation of a large number of uniform and fine nanocrystals in the amorphous matrix, thereby optimizing its soft magnetic properties. This type of material has broad application prospects in electronics, electricity, communications and other fields due to its excellent properties such as high saturation magnetization and low coercivity. However, in order to achieve these properties, traditional methods often require the introduction of expensive elements such as cobalt (Co) and nickel (Ni). Although these elements as trace elements can effectively improve the magnetic properties of the material, they significantly increase the material cost. Due to the multi-step process and strict temperature control involved, the entire preparation process can be very time-consuming, thereby reducing the production speed. In addition, the existing method may require multiple steps, such as repeated heating and cooling, to obtain the desired nanocrystalline structure, which will significantly reduce production efficiency.

[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0005] Based on this, the present application provides an amorphous alloy material and a preparation method thereof, as well as a magnetic alloy product that simultaneously maintains an amorphous structure and excellent soft magnetic properties.

[0006] This application is implemented through the following technical solutions:

[0007] In one aspect of the present application, an amorphous alloy material is provided, wherein the chemical composition of the amorphous alloy material is Fe a P b B c C d Cu e , where a, b, c, d, and e represent the atomic percentage of each element, 70≤a≤80, 0≤b≤14, 0≤c≤14, 3≤d≤6, 0<e≤2, and a+b+c+d+e=100.

[0008] In some of the embodiments, 75≤a≤80, 7≤b≤14, 0≤c≤7, 3≤d≤6, 0<e≤2.

[0009] Another aspect of the present application also provides a method for preparing an amorphous alloy material, comprising the following steps:

[0010] Weighing raw materials according to the element composition ratio of the amorphous alloy material, placing them in a smelting furnace for smelting treatment, and casting to obtain an alloy ingot;

[0011] remelting the alloy ingot to obtain an alloy melt;

[0012] The alloy melt is formed and cooled to obtain an alloy strip;

[0013] The alloy strip is subjected to heat treatment to obtain an amorphous alloy material.

[0014] In some of the embodiments, in the remelting step, the alloy ingot is placed in a quartz tube with a nozzle at the bottom for remelting.

[0015] In some of the embodiments, in the shaping and cooling step, the alloy melt is sprayed onto a rotating copper roller through a nozzle at the bottom of the quartz tube to cool the alloy melt into shape.

[0016] In some of these embodiments, at least one of the conditions (1) to (3) is satisfied:

[0017] (1) The diameter of the nozzle is 0.5 mm to 1.5 mm;

[0018] (2) The distance between the nozzle and the copper roller is 0.2 mm to 0.3 mm;

[0019] (3) The copper wheel linear speed of the copper roller is 40 m / s to 50 m / s.

[0020] In some embodiments, the smelting treatment conditions are: smelting at a temperature of 1500° C. to 1600° C. for 30 min to 120 min in a protective gas;

[0021] And / or, the remelting treatment conditions are: melting at a temperature of 1100° C. to 1250° C. for 30 min to 120 min in a protective gas.

[0022] In some of the embodiments, the alloy strip has a completely amorphous structure.

[0023] In some embodiments, the heat treatment conditions are: annealing at a temperature of 500° C. to 600° C. for 1 h to 4 h in a vacuum state.

[0024] One aspect of the present application further provides a magnetic alloy product, which includes the above-mentioned amorphous alloy material or an amorphous alloy material prepared by the above-mentioned method for preparing the amorphous alloy material.

[0025] The elements of the amorphous alloy material of the present application include specific components with a specific ratio relationship, wherein the iron element gives the alloy certain magnetic properties; the phosphorus element helps to lower the melting point of the alloy, making the alloy easier to melt and form during the preparation process, and phosphorus may affect the atomic arrangement of the alloy, promote the alloy to form an amorphous structure during rapid cooling, and may also have a certain impact on the chemical stability and mechanical properties of the alloy; the boron element significantly reduces the melting point of the alloy, and during the rapid cooling process, helps the alloy atoms to form an amorphous state without having time to arrange into a crystal structure; the carbon element can improve the hardness of the alloy to a certain extent, so that it exhibits better performance in terms of wear resistance and deformation resistance; the copper element promotes the solidification process of the alloy, helps to obtain a more uniform microstructure, and makes the alloy more stable in performance. The various components are coordinated and coordinated through a specific ratio relationship, so that the amorphous alloy material simultaneously maintains an amorphous structure and excellent soft magnetic properties. And the phosphorus element is used in the above-mentioned amorphous alloy material, and the cobalt element is not used, which reduces the cost while maintaining excellent soft magnetic properties.

[0026] Furthermore, the preparation process of the amorphous alloy material is simple and easy to implement, and the prepared amorphous alloy material can adapt to existing production processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD diffraction pattern of the free surface of the alloy strips prepared in Examples 1 and 2 of the present application. DETAILED DESCRIPTION

[0028] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0030] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0031] An embodiment of the present application provides an amorphous alloy material, the chemical composition of the amorphous alloy material is Fe a P b B c C d Cu e , where a, b, c, d, and e represent the atomic percentage of each element, 70≤a≤80, 0≤b≤14, 0≤c≤14, 3≤d≤6, 0<e≤2, and a+b+c+d+e=100.

[0032] The elements of the amorphous alloy material of the present application include specific components with a specific ratio relationship, wherein the iron element gives the alloy certain magnetic properties; the phosphorus element helps to lower the melting point of the alloy, making the alloy easier to melt and form during the preparation process, and phosphorus may affect the atomic arrangement of the alloy, promote the alloy to form an amorphous structure during rapid cooling, and may also have a certain impact on the chemical stability and mechanical properties of the alloy; the boron element significantly reduces the melting point of the alloy, and during the rapid cooling process, helps the alloy atoms to form an amorphous state without having time to arrange into a crystal structure; the carbon element can improve the hardness of the alloy to a certain extent, so that it exhibits better performance in terms of wear resistance and deformation resistance; the copper element promotes the solidification process of the alloy, helps to obtain a more uniform microstructure, and makes the alloy more stable in performance. The various components are coordinated and coordinated through a specific ratio relationship, so that the amorphous alloy material simultaneously maintains an amorphous structure and excellent soft magnetic properties. And the phosphorus element is used in the above-mentioned amorphous alloy material, and the cobalt element is not used, which reduces the cost while maintaining excellent soft magnetic properties.

[0033] In some of the embodiments, 75≤a≤80, 7≤b≤14, 0≤c≤7, 3≤d≤6, 0<e≤2.

[0034] Further controlling the element composition of the amorphous alloy material within the above range can further improve the amorphous structure and excellent soft magnetic properties of the amorphous alloy material.

[0035] Compared with traditional amorphous alloys, the Fe-based amorphous nanocrystals proposed in this application successfully reduce the cost of Fe-based amorphous nanocrystal core materials by replacing the Co element with P, while maintaining their amorphous structure and potential excellent soft magnetic properties.

[0036] An embodiment of the present application further provides a method for preparing an amorphous alloy material, comprising the following steps S10 to S40.

[0037] S10, weighing raw materials according to the element composition ratio of the amorphous alloy material, placing them in a smelting furnace for smelting treatment, and casting to obtain an alloy ingot.

[0038] It should be noted that the melting furnace used above can be an induction melting furnace commonly used in the art, such as a vacuum induction melting furnace.

[0039] The vacuum induction melting furnace mainly uses high-frequency alternating current to excite the alternating magnetic field in the induction coil, and uses the electromagnetic induction phenomenon to form eddy currents in the smelting crucible to heat and melt the raw materials. The use of an induction vacuum melting furnace can effectively reduce the burning of alloy materials and avoid oxidation caused by direct contact between raw materials and air during the smelting process, which causes deviations in the composition of the master alloy; at the same time, the heat exchange loss of vacuum induction melting is small, which can improve the smelting efficiency and reduce the energy consumption generated during the smelting process.

[0040] In some of the embodiments, the smelting treatment conditions are: smelting at a temperature of 1500° C. to 1600° C. for 30 min to 120 min in a protective gas.

[0041] It is understood that when a numerical range is disclosed herein, the above range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0042] It should be noted that the temperature range of the smelting treatment is "1500°C~1600°C", that is, the minimum and maximum values ​​of the range of 1500°C~1600°C, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and the following point values: 1500°C, 1505°C, 1510°C, 1515°C, 1520°C, 1525°C, 1530°C, 1535°C, 1540°C, 1545°C, 1550°C, 1555°C, 1560°C, 1565°C, 1570°C, 1575°C, 1580°C, 1585°C, 1590°C, 1595°C or 1600°C; or a range consisting of any two of these values. As an example, 1550°C~1600°C.

[0043] The time range of the smelting treatment is "30min~120min", which means that the minimum and maximum values ​​in the range of 30min~120min, and each value between the minimum and maximum values, can be taken. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 30min, 35min, 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min, 80min, 85min, 90min, 95min, 100min, 105min, 110min, 115min, 120min; or a range consisting of any two of these values. As an example, 60min~120min.

[0044] S20, remelting the alloy ingot to obtain an alloy melt.

[0045] In some of the embodiments, in the remelting step, the alloy ingot is placed in a quartz tube with a nozzle at the bottom for remelting.

[0046] In some of the embodiments, the remelting treatment conditions are: melting at a temperature of 1100° C. to 1250° C. for 30 min to 120 min in a protective gas.

[0047] The temperature range of the remelting treatment is "1100°C~1250°C", that is, the minimum value and the maximum value of the range of 1100°C~1250°C, and every value between the minimum value and the maximum value. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 1100°C, 1105°C, 1115°C, 1120°C, 1125°C, 1130°C, 1135°C, 1140°C, 1145°C, 1150°C, 1155°C, 1160°C, 1165°C, 1170°C, 1175°C, 1180°C, 1185°C, 1190°C, 1195°C, 1200°C, 1205°C, 1210°C, 1215°C, 1220°C, 1225°C, 1230°C, 1235°C, 1240°C, 1245°C or 1250°C; or a range consisting of any two of these values. As an example, 1150°C to 1200°C.

[0048] S30, forming and cooling the alloy melt to obtain an alloy strip.

[0049] In some of the embodiments, in the molding and cooling step, the alloy melt is sprayed onto a rotating copper roller through a nozzle at the bottom of the quartz tube to cool the alloy melt into shape.

[0050] In some embodiments, the diameter of the nozzle is 0.5 mm to 1.5 mm.

[0051] The range of the nozzle diameter is "0.5mm~1.5mm", which means the minimum and maximum values ​​in the range of 0.5mm~1.5mm, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiment and the following point values: 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm or 1.5mm; or a range consisting of any two of these values. As an example, 1mm~1.5mm.

[0052] In some embodiments, the distance between the nozzle and the copper roller is 0.2 mm to 0.3 mm.

[0053] The distance between the nozzle and the copper roller is in the range of "0.2mm~0.3mm", that is, the minimum and maximum values ​​in the range of 0.2mm~0.3mm, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiment and the following point values: 0.2mm, 0.21mm, 0.22mm, 0.23mm, 0.24mm, 0.25mm, 0.26mm, 0.27mm, 0.28mm, 0.29mm or 0.3mm; or a range consisting of any two of these values. As an example, 0.2mm~0.25mm.

[0054] In some embodiments, the copper wheel linear speed of the copper roller is 40 m / s to 50 m / s.

[0055] The value range of the copper wheel linear speed of the copper roller is "40 m / s ~50 m / s", that is, the minimum and maximum values ​​in the range of 40 m / s ~50 m / s, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiment and the following point values: 40 m / s, 41 m / s, 42 m / s, 43 m / s, 44 m / s, 45 m / s, 46 m / s, 47 m / s, 48 ​​m / s, 49 m / s or 50 m / s; or a range consisting of any two of these values. As an example, 40m / s~45m / s.

[0056] In some embodiments, the alloy strip has a completely amorphous structure.

[0057] S40, heat treating the alloy strip to obtain an amorphous alloy material.

[0058] In some embodiments, the heat treatment conditions are: annealing at a temperature of 500° C. to 600° C. for 1 h to 4 h in a vacuum state.

[0059] An embodiment of the present application further provides a magnetic alloy product, wherein the magnetic alloy product comprises the amorphous alloy material or an amorphous alloy material prepared by the method for preparing the amorphous alloy material.

[0060] The above-mentioned amorphous alloy material and its preparation method, when used to prepare magnetic alloy products, have excellent soft magnetic properties such as high saturation magnetization intensity and low coercive force, and can meet the requirements of equipment high efficiency, energy saving and environmental protection.

[0061] In some examples, the magnetic alloy products include, but are not limited to, electromagnetic devices, transformer devices, inductor devices, mutual inductor devices, wireless charging devices, and magnetic recording devices.

[0062] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0063] In order to better illustrate the present invention, the content of the present invention is further described below in conjunction with embodiments.

[0064] Example 1

[0065] In this embodiment, for FeCoBCCu amorphous alloy, P is used to replace Co element, and the molecular formula is: Fe 78.8 P 14 C 6 Cu 1.2 The preparation method of the Fe-based amorphous nanocrystalline alloy is as follows:

[0066] (1) Pure iron (99.99wt.%), Cu (99.995wt.%), B (99.99wt.%), Fe-C alloy (96wt.%Fe and 4wt.%C), and iron-phosphorus alloy (71.62wt.%Fe and 25.23wt.%P) were prepared according to the mass percentage content in the above amorphous alloy material expression, and the raw materials were cleaned.

[0067] (2) The above ingredients were placed in a vacuum induction melting furnace and smelted at a temperature of 1550°C in an argon atmosphere at a flow rate of 10 L / min for 60 min. After casting, an alloy ingot was obtained.

[0068] (3) The alloy ingot is then placed in a quartz tube with a nozzle at the bottom for remelting. The melting temperature is set to 1150°C and the melting time is 60 minutes. The master alloy in the quartz tube is heated by an induction coil until the alloy is completely melted to obtain an alloy melt.

[0069] (4) High-pressure argon gas is then injected into the quartz tube to spray the liquid alloy melt onto the high-speed rotating copper roller. The rotating copper roller is used to quickly cool the melt. The argon injection pressure is controlled to be 0.03 MPa, the copper wheel linear speed is 45 m / s, the nozzle size is 1 mm, and the distance between the nozzle and the copper wheel is 0.3 mm to obtain an alloy strip.

[0070] (5) Under vacuum protection, isothermal annealing treatment is performed. The annealing temperature can be set at 600°C and kept for 2 hours to obtain an amorphous alloy material.

[0071] (6) Test the physical and chemical properties of the prepared amorphous alloy materials.

[0072] Example 2

[0073] In this embodiment, for FeCoBCCu amorphous alloy, P is used to replace Co element, and the molecular formula is: Fe 78.8 P 7 B 7 C 6 Cu 1.2 The preparation method of the Fe-based amorphous nanocrystalline alloy is as follows:

[0074] (1) Pure iron (99.99wt.%), Cu (99.995wt.%), B (99.99wt.%), Fe-C alloy (96wt.%Fe and 4wt.%C), and iron-phosphorus alloy (71.62wt.%Fe and 25.23wt.%P) were prepared according to the mass percentage content in the above amorphous alloy material expression, and the raw materials were cleaned.

[0075] (2) The above ingredients were placed in a vacuum induction melting furnace and smelted at a temperature of 1550°C in an argon atmosphere at a flow rate of 10 L / min for 60 min. After casting, an alloy ingot was obtained.

[0076] (3) The alloy ingot is then placed in a quartz tube with a nozzle at the bottom for remelting. The melting temperature is set to 1150°C and the melting time is 60 minutes. The master alloy in the quartz tube is heated by an induction coil until the alloy is completely melted to obtain an alloy melt.

[0077] (4) High-pressure argon gas is then injected into the quartz tube to spray the liquid alloy melt onto the high-speed rotating copper roller. The rotating copper roller is used to quickly cool the melt. The argon injection pressure is controlled to be 0.03 MPa, the copper wheel linear speed is 45 m / s, the nozzle size is 1 mm, and the distance between the nozzle and the copper wheel is 0.3 mm to obtain an alloy strip.

[0078] (5) Under vacuum protection, isothermal annealing treatment is performed. The annealing temperature can be set at 600°C and kept for 2 hours to obtain an amorphous alloy material.

[0079] (6) The physical and chemical properties of the prepared amorphous alloy material are tested; the following are the specific performance tests.

[0080] 1. The alloy strip prepared as above is characterized by X-ray diffraction for phase structure: X-ray diffraction analysis (XRD) is the most commonly used method for characterizing the phase structure of materials. When X-rays of a certain wavelength are irradiated onto the surface of the sample, the electrons are forced to vibrate due to encountering internal atoms or ions, resulting in coherent scattering. The scattered waves of different atoms interfere with each other, and strong X-ray diffraction will be generated in certain special directions, showing a specific diffraction pattern corresponding to the internal structure. By comparing it with the known material spectrum, the crystal structure and physicochemical composition of the sample can be determined. Crystalline materials will have sharp diffraction peaks, while amorphous materials will show broad "steamed bun"-shaped diffuse scattering peaks. This application uses the D8-Discover X-ray diffractometer produced by Bruker AXS, Germany. The test conditions are as follows: anode target material: Cu target, Kα radiation, incident light wavelength λ=1.54056 Å; tube voltage 40 kV, tube current 40 mA; test step length 0.02°, angle range 30-90°, scan rate 0.15 step / s.

[0081] 2. Test the saturation magnetic induction intensity of the amorphous alloy material prepared above: The saturation magnetic induction intensity (Bs) of the samples in this article is measured by Lake Shore 7410 vibrating sample magnetometer (VSM), and the maximum test magnetic field is selected as 800 kA / m. VSM uses the principle of electromagnetic induction to measure the change of magnetic moment of magnetic samples in a magnetic field, and is the most widely used high-sensitivity magnetic measuring instrument. The test principle is as follows: cut 2-3 mg of strip sample, and use double-sided tape to stick the sample in a cross shape to the bottom of the vibration rod to eliminate the anisotropy effect as much as possible; place the vibration rod in the electromagnet, and the sample is uniformly magnetized by the uniform magnetic field generated by the ferromagnet; when the oscillator outputs power, the vibration rod will drive the sample to vibrate in the magnetic field, so that the dipole field generated by the magnetized sample vibrates relative to the detection coil, thereby generating an induced electromotive force in the fixed detection coil. Considering that the sample size is very small, its induced electromotive force is proportional to the sample magnetic moment, vibration frequency and amplitude. Therefore, when the vibration frequency and amplitude remain unchanged, the relevant magnetic moment of the sample can be calculated by measuring the induced electromotive force with a phase-locked amplifier. The hysteresis loop and saturation magnetic induction intensity of the sample can be obtained through the relationship between the magnetic field and the magnetic moment.

[0082] Coercivity test

[0083] 3. Test the coercivity of the amorphous alloy material prepared above: The coercivity (Hc) of the samples in this article is measured using the EXPH-100 DC BH analyzer produced by RIKEN, Japan. Although VSM can also test the coercivity of samples, the applied magnetic field is too large (800 kA / m), which is much larger than the soft magnetic properties of the sample itself, and cannot truly reflect the coercivity of the sample. Therefore, a DC BH analyzer is used for accurate measurement under a small field (1 kA / m). The strip sample adopts a non-closed magnetic circuit test method, using a matching sample stage, and the test length is generally 6-8 cm; the ring core sample adopts a closed magnetic circuit test method.

[0084] Figure 1 It is quenched Fe 78.8 P 14-x B x C 6 Cu 1.2 (x=0, 7at.%) X-ray diffraction pattern of the free surface of the amorphous alloy strip. From the figure, it can be seen that there are no sharp diffraction peaks in the two curves, and only a wide diffraction peak shaped like a steamed bun appears near the diffraction angle of 2θ=44º. The amorphous state is a state of short-range order and long-range disorder. Its crystalline phase is different from the crystal diffraction spectrum with a series of sharp diffraction peaks, but only has a diffusely scattered "steamed bun" peak, which indicates that the prepared sample is a completely amorphous structure.

[0085] Compared with traditional amorphous alloys, the Fe-based amorphous nanocrystals proposed in this application have successfully reduced the cost of Fe-based amorphous nanocrystal magnetic core materials by replacing the Co element with P, while maintaining their amorphous structure and excellent soft magnetic properties. Fe-based amorphous nanocrystals have high hardness, high strength and excellent toughness, high saturation magnetization intensity and low coercive force and other excellent soft magnetic properties, which can meet the actual application of the product.

[0086] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An amorphous alloy material, characterized in that: The chemical composition of the amorphous alloy material is Fe a P b B c C d Cu e , where a, b, c, d, and e represent the atomic percentage of each element, 70≤a≤80, 0≤b≤14, 0≤c≤14, 3≤d≤6, 0<e≤2, and a+b+c+d+e=100.

2. The amorphous alloy material according to claim 1, characterized in that: 75≤a≤80, 7≤b≤14, 0≤c≤7, 3≤d≤6, 0<e≤2.

3. The method for preparing the amorphous alloy material according to any one of claims 1 to 2, characterized in that: The steps include: Weighing raw materials according to the element composition ratio of the amorphous alloy material, placing them in a smelting furnace for smelting treatment, and casting to obtain an alloy ingot; remelting the alloy ingot to obtain an alloy melt; The alloy melt is formed and cooled to obtain an alloy strip; The alloy strip is subjected to heat treatment to obtain an amorphous alloy material.

4. The method for preparing an amorphous alloy material according to claim 3, characterized in that: In the remelting step, the alloy ingot is placed in a quartz tube with a nozzle at the bottom for remelting.

5. The method for preparing an amorphous alloy material according to claim 4, characterized in that: In the shaping and cooling step, the alloy melt is sprayed onto a rotating copper roller through a nozzle at the bottom of the quartz tube to cool the alloy melt into shape.

6. The method for preparing an amorphous alloy material according to claim 5, characterized in that: Satisfy at least one of the following conditions: (1) The diameter of the nozzle is 0.5 mm to 1.5 mm; (2) The distance between the nozzle and the copper roller is 0.2 mm to 0.3 mm; (3) The copper wheel linear speed of the copper roller is 40 m / s to 50 m / s.

7. The method for preparing an amorphous alloy material according to any one of claims 3 to 6, characterized in that: The smelting treatment conditions are: smelting at a temperature of 1500° C. to 1600° C. for 30 min to 120 min in a protective gas; And / or, the remelting treatment conditions are: melting at a temperature of 1100° C. to 1250° C. for 30 min to 120 min in a protective gas.

8. The method for preparing an amorphous alloy material according to any one of claims 3 to 6, characterized in that: The alloy strip has a completely amorphous structure.

9. The method for preparing an amorphous alloy material according to any one of claims 3 to 6, characterized in that: The heat treatment conditions are: annealing at a temperature of 500° C. to 600° C. for 1 h to 4 h in a vacuum state.

10. A magnetic alloy product, characterized in that: The magnetic alloy product comprises the amorphous alloy material as described in any one of claims 1 to 2 or an amorphous alloy material prepared by the method for preparing the amorphous alloy material as described in any one of claims 3 to 9.

Citation Information

Cited By

  • Method for preparing excellent soft magnetic amorphous nanocrystalline alloy based on lunar soil crystallization phenomenon and soft magnetic amorphous nanocrystalline alloy

    CN120261100A